'Pulsing' cities and 'swarming' metropolises: A simplified, entropy-based approach to long-term urban development. (March 2022) - Sadat Nickayin, Samaneh; Bianchini, Leonardo; Egidi, Gianluca; Cividino, Sirio; Rontos, Kostas; Salvati, Luca
Highlights: Urban transformations are associated with a broad spectrum of economic conditions. This study links regional science with ecological metrics. We identified non-linear stages of the metropolitan cycle in a Mediterranean city. Urban expansion is a recursive process with sequential accelerations and decelerations. Spatial planning is required to give adaptive responses to local development. Abstract: Relocating activities along the fringe, re-designing economic functions, and re-modelling settlement structures across larger regions and broader spatial scales, reflect the inherent shift toward complex metropolitan systems. A refined understanding of urban change requires the adoption of a 'complex thinking' that focuses on adaptive behaviour of key agents and local development networks within highly volatile real estate markets. By linking ecology with regional science, our study investigates speed and spatial direction of building activity rates introducing original indicators of urban growth and an exploratory multivariate statistics of the evolving socioeconomic context in the Athens' region, Greece. Having experienced spatially uncoordinated growth that often resulted in self-organised settlements and socially diversified neighbourhoods, Athens was a paradigmatic example of complex metropolitan systems in Europe. The empirical findings of our study identify non-linear stages of the metropolitan cycle supporting the assumption that long-term urban expansion is a recursive process, with irregular accelerations and decelerations, and a complex relationship between spatial and temporal dimensions. Urban transformations are associated with a broad spectrum of socioeconomic conditions. While playing a variable role over the last century, the most relevant factors in Athens' growth include population dynamics, urban concentration, and wealth accumulation. Considering such dynamics, spatial planning is required to give adaptive responses to discontinuous socioeconomic development increasingly dependent on territorial aspects and environmental constraints.